PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL TERHADAP KEMAMPUAN MENULIS CERPEN KELAS V B SDN TENGGILIS MEJOYO I SURABAYA - Nurwindasari, Dian Ayu; Sumiharsono, Rudy; Danang Prastyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research uses a causal quantitative method with a posttest-only research design. This research has a problem formulation: Is there an influence of the use of audiovisual media on the ability to write short stories for class V B, SDN Tenggilis Mejoyo I Surabaya. This research aims to find out whether there is an influence of the use of audiovisual media on the ability to write short stories for class V B at SDN Tenggilis Mejoyo I Surabaya. This research used a population of all class V students at SDN Tenggilis Mejoyo I Surabaya, totaling 60 students. The sample used was 30 class V B students as the main respondents and 30 class V A students as supporting respondents used in the research. This research has variable X, namely audiovisual media and variable Y, Short Story Writing Ability. This research was motivated by the problem of the short story writing ability of class V students at SDN Tenggilis Mejoyo I Surabaya which was still relatively low. Some students are not enthusiastic about writing because of the lack of supporting facilities (learning media). Data collection techniques use questionnaires, tests, interviews, observation and documentation. Instrument testing uses validity and reliability. Prerequisite tests use the normality test and homogeneity test. Test the hypothesis in the form of a Paired Sample T-Test t test. To find out the distribution value of the t table, look at it based on df = 28 with a level of a = 0.05. Because the calculated t value > t table (86,252 > 1.70113) and Sig (2-tailed) 0.00 < 0.05, H0 is rejected. This means that the hypothesis states a significant influence regarding the use of audiovisual media on the ability to write short stories for class V SDN Tenggilis Mejoyo I Surabaya.